Effect of Chinese chives (Allium tuberosum) addition to carboxymethyl cellulose based food packaging films. (1st May 2020) - Riaz, Asad; Lagnika, Camel; Luo, Hao; Nie, Meimei; Dai, Zhuqing; Liu, Chunquan; Abdin, Mohamed; Hashim, Malik Muhammad; Li, Dajing; Song, Jiangfeng
Highlights: CMC-based food packaging films were developed by incorporation of CRE. Prepared films were characterized by SEM, XRD, DSC and TGA. Antimicrobial and antioxidants activities of prepared films were also evaluated. CMC-based CRE films improved in terms of physical properties and WVP. CRE can be used as antimicrobial and antioxidant agent to develop CMC-based films. Abstract: Carboxymethyl cellulose (CMC) based novel functional films containing Chinese chives root extract (CRE) at different concentrations (1, 3 and 5 % in w/w) were successfully fabricated. It was revealed by SEM that higher extract concentration triggered the formation of agglomerates within the film. Tensile strength of the films was decreased from 30.91 to 16.48 MPa. Thickness of films was increased from 43 to 84 μm, while decrease in water solubility from 77.51–52.91 %, swelling degree from 55.74 to 40.37 %, and water vapor permeability from 5.76 to 1.17 10 −10 gm -1 s -1 Pa -1 was observed. DPPH and ABTS radical scavenging ability of CMC-CRE films was increased from 0 to 58 % and 82 %, respectively. CMC-CRE5 film showed the highest biodegradability of 58.14 %. The film prepared by the addition of CRE into CMC also exhibited good antioxidant and antimicrobial activity indicating that it could be developed as a bio-composite food packaging material for the food industry.